Is Generative AI Possible Cause of the Swan Song of the Rational Civilisation? - Mścisławski Łukasz (Studies in Logic, Grammar and Rhetoric)
Despite the many successes of generative AI, a number of fundamental questions have begun to arise around this technology. There is undoubtedly an interesting situation from a philosophical point of view. It can be carefully assumed that contemporary digital information processing technologies have arisen inside a circle of civilisation, one of the foundations of which is the classical account of truth. This account, even if seen as ideal and absolute, nevertheless seems to be a driving force in the field of science. Is it possible that generative AI will result in the replacement of the pursuit of truth by a mere uncritical adherence to the results provided by AI systems, as well as the inhibition of lively creativity both scientific and artistic?